O construtivismo kantiano segundo a interpretação de John Rawls - Teixeira, Tedson Mayckell Braga (2018)
In the late 1970s, John Rawls began building the theoretical edifice of notabilization around 20 years later as one of the greatest examples of the philosophy of the century's history. He advocates a new design of social issues as primarily material, ethical, and symbolic distortions in a society are equated through a global model universally available to all members of a community. By this means we would have the creation of principles of justice, in which anyone can give his free and high consent that corroborates or rejects his general sense of coexistence. Rawls classifies himself as an example of a patent of moral constructivism, and then joins Kantian moral philosophy, which, according to the American philosopher, is the primordial domain of constructivist doctrine, more so than as mathematics. It is precisely at this particular point that we turn our attention to this work: How constructivist, in fact, is Kant's thought? Are the Rawls, the interpretation that is incredibly fruitful at the end of the last century, not committing to graves or generalizations, by treating as epistemologically related areas of methodologies distinct from Kantian thought? It is one of the characteristics of the knowledge and thematic themes that involve knowledge, knowledge, pure rational, both theoretical and moral, and mainly as mathematics, for later analysis of the critique of the merits and restrictions of interpretation that direct our efforts. Initially referred to by Kant only in mathematics (geometry, arithmetic and algebra), his work consists of analyzing the sufficiency of a didactic methodology for Kantian moral philosophy, thus determining until the text of the Prussian philosopher is interpreted.